2016
DOI: 10.5603/fm.a2016.0026
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes in the vulva and vagina from ovariectomised rats undergoing oestrogen treatment

Abstract: Estradurin or Sintofolin. (Folia Morphol 2016; 74, 4: 467-473)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
1
3
0
2
Order By: Relevance
“…The histological analysis in our study revealed that the structural properties of the vaginal wall, including the epithelium, lamina propria, muscularis, and adventitia layers, are similar between rats and humans, thus providing a foundation for observing the impact of menopause on the vaginal wall. Mocan-Hognogi et al proved that surgically induced anestrus started 15 days after bilateral ovariectomy by detecting significantly decreased estradiol levels after surgery [19]. We also found that the epithelium began to atrophy 2 weeks after ovariectomy, which is consistent with previous studies [24, 25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The histological analysis in our study revealed that the structural properties of the vaginal wall, including the epithelium, lamina propria, muscularis, and adventitia layers, are similar between rats and humans, thus providing a foundation for observing the impact of menopause on the vaginal wall. Mocan-Hognogi et al proved that surgically induced anestrus started 15 days after bilateral ovariectomy by detecting significantly decreased estradiol levels after surgery [19]. We also found that the epithelium began to atrophy 2 weeks after ovariectomy, which is consistent with previous studies [24, 25].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we conducted a comprehensive analysis of rat vaginal wall changes by combining histological, biochemical, and biomechanical analyses both short- and long-term after surgically inducing menopause. In this study, we used an experimental rat model of surgically induced menopause through bilateral ovariectomy to form permanent anestrus [17, 19]. A previous study found that age had a significant effect on the response of the vagina and its supportive tissues to ovariectomy such that ovariectomy significantly affected these tissues in young rats but not in middle-aged rats [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were especially interested in the correlation between MCit and ER + carcinoma cells, as some studies have proved that estrogen activates mast cells in ovarian endometriosis and that human uterine mast cells express ERβ (19,20). Others have shown that administration of estrogens leads to eosinophilic and MCs infiltrations (21). MCs play a pro-tumorigenic role in human bladder cancer through stimulating ERβ and it has been demonstrated in a murine model of bladder cancer that a selective ERβ antagonist can inhibit mast cell-promoted tumor growth (9).…”
Section: Cells (Mcs) In Breast Carcinomas Stained For Anti-tryptase (mentioning
confidence: 99%
“…Entretanto, esse efeito não foi observado nas usuárias de COC, porém a morfologia vaginal não foi avaliada (ZALENSKAYA et al, 2018). Em animais, a maioria dos estudos diz respeito à avaliação do trofismo vaginal em modelos de menopausa cirúrgica, já que este quadro causa grave atrofia da mucosa vaginal (BENOIT et al, 2017;HENRIQUES et al, 2011;MOCAN-HOGNOGI et al, 2016). Assim, pouco se sabe a respeito da ação dos COC sobre a morfologia vaginal na idade reprodutiva.…”
Section: Discussionunclassified